Replication Pilot Trial of Therapeutic Horseback Riding and Cortisol Collection With Children on the Autism Spectrum - Pan, Zhaoxing; Granger, Douglas A.; Guérin, Noémie A.; Shoffner, Amy; Gabriels, Robin L. (Frontiers in Veterinary Science, 2019)
We aimed to determine whether results of our prior randomized control trial [RCT; NCT02301195, (1)] of Therapeutic Horseback Riding (THR) for children and adolescents with autism spectrum disorder (ASD) could be replicated at a different riding center and if treatment effects also included differences in the expression of associations between problem behavior and the activity of the hypothalamic-pituitary-adrenal (HPA) axis. Participants with ASD (N = 16) ages 6-16 years were randomized by nonverbal intelligence quotient to either a 10-week THR group (n = 8) or no horse interaction barn activity (BA) control group (n = 8). Outcome measures were a standard speech-language sample and caregiver-report of aberrant and social behaviors. Participants' saliva was sampled weekly at a consistent afternoon time immediately pre- and 20 min' post-condition (later assayed for cortisol). Intent-to-treat analysis revealed that compared to controls, THR participants had significant improvements in hyperactivity, and social awareness, and significant improvements at the 0.1 significance level in irritability and social communication behaviors. There were no significant improvements in number of words or new words spoken during the standard language sample. Linear mixed effects model analysis indicated that greater weekly pre-lesson irritability levels were associated with smaller post-lesson reduction in salivary cortisol levels, and greater weekly pre-lesson hyperactivity levels were associated with smaller cortisol reduction in the THR group, but not in the BA control group. The findings represent a partial replication of prior results (1), extend prior observations to include THR effects on biobehavioral relationships and suggest that cortisol could be a target mediator for THR effects on irritability and hyperactivity behaviors in youth with ASD. Clinical Trial Registration: Trial of Therapeutic Horseback Riding in Children and Adolescents with Autism Spectrum Disorder; http://clinicaltrials.gov, identifier: NCT02301195